2018
DOI: 10.1556/0806.45.2017.063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of golden and brown linseed fibre on wheat flour pasting, dough properties and bread quality

Abstract: Wheat flour was enhanced by linseed fibre, characterised by granulation 500-700 μm. Using seeds from 2015 flax harvest, linseed fibre was gained from two golden and one brown linseed varieties (Amon, Raciol and Recital, respectively). Additions at levels 2.5% and 5.0% affected amylases activity and protein technological quality softly, evaluated by Falling Number and Zeleny sedimentation tests, respectively. Both brown and yellow linseed fibre significantly supported extensograph elasticity of non-fermented do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For example, by-products from the flaxseed industrywere applied in wheat flour formulation of bread, and these results confirmed the usefulness of these residues in bakery production [22][23][24]. Other authors have also confirmed the possibility of using linseed fibre [17,19] or flaxseed flour addition [16,18,21]. Although flaxseeds and linseed products have been used in the production of bread, there are no clear guidelines for choosing grinders.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…For example, by-products from the flaxseed industrywere applied in wheat flour formulation of bread, and these results confirmed the usefulness of these residues in bakery production [22][23][24]. Other authors have also confirmed the possibility of using linseed fibre [17,19] or flaxseed flour addition [16,18,21]. Although flaxseeds and linseed products have been used in the production of bread, there are no clear guidelines for choosing grinders.…”
Section: Introductionmentioning
confidence: 82%
“…Flaxseeds, linseed flour, and other products from these seeds were used in different bread formulations and caused beneficial changes in rheological [16] and sensory evaluation [17][18][19][20][21]. For example, by-products from the flaxseed industrywere applied in wheat flour formulation of bread, and these results confirmed the usefulness of these residues in bakery production [22][23][24].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The pasting properties of starch might give useful information related to the quality of bakery products and should be investigated to establish alternative methods for the prediction of baking quality (Koksel et al, 2009). Mixolab has been applied for prediction and suitability of flours for different end-uses, e.g., the cookie and cake quality (Kahraman et al, 2008;Ozturk et al, 2008), the effect of antioxidants on dough mixing properties (Abdel-Samie et al, 2010), linseed fibre on wheat flour pasting and bread quality (Švec, Hrušková, 2018). The information related to Mixolab use for the evaluation of different aspects of hulled wheat flour quality is very limited (Bernas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%